2019
DOI: 10.1016/j.bj.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of IL-1Ra on intestinal ischemia reperfusion injury by anti-oxidative stress via Nrf2/HO-1 pathway in rat

Abstract: Background Intestinal ischemia reperfusion injury is a frequent clinical damage, in which the oxidative stress and inflammation play an important role. Interleukin-1 receptor antagonist (IL-1Ra) is a natural anti-inflammatory factor, however, its effect on intestinal ischemia reperfusion injury remains unclear. Methods The rat model of intestinal I/R was induced by occlusion (for 60 min) and reopening (for 60 min) of superior mesenteric artery. The rats were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…41 Previous studies have shown that IL-1Ra significantly inhibits CI/ R-induced oxidative stress by promoting the expression of Nrf2 and HO-1. 42 Similarly, this study found that Nrf2 pathway was inactivated in CI/R rats. Interestingly, CGA reactivated Nrf2 pathway and promoted Nrf2, HO-1 and NQO-1 expression, which further increased SOD activity and reduced MDA level.…”
Section: Discussionsupporting
confidence: 56%
“…41 Previous studies have shown that IL-1Ra significantly inhibits CI/ R-induced oxidative stress by promoting the expression of Nrf2 and HO-1. 42 Similarly, this study found that Nrf2 pathway was inactivated in CI/R rats. Interestingly, CGA reactivated Nrf2 pathway and promoted Nrf2, HO-1 and NQO-1 expression, which further increased SOD activity and reduced MDA level.…”
Section: Discussionsupporting
confidence: 56%
“…Instead, encapsulated-hAMSCs only overproduced PIGF-1 significantly, while the expression of the other factors was comparable to that of 2D cultures. IL-1RA was shown to have protective effects through its anti-inflammatory and antioxidative mechanisms in an in vivo rat model of IRI [ 63 ], where IL-1RA not only effectively inhibited the expression of inflammatory factors, such as IL-1β, IL-6, and TNF-α, but it also decreased the death of damaged cells in intestinal tissues. It has been shown that both human and mouse pluripotent stem cells attenuate the apoptosis/necrosis and potentiate cell proliferation through different anti-inflammatory and growth factors, such as IL-10, FGF, EGF, and HGF [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the repair effect of Rut on CI/R injury may be achieved by promoting the expression of CGRP and activation of Nrf2 pathway, and inhibiting the activation of ERK1/2 pathway.It has been reported that the Nrf2/HO-1 pathway has a significant protective effect on I/R injury 18. Jin et al found that IL-1ra inhibits oxidative stress and inflammation caused by I/R injury by promoting the expression of Nrf2 and HO-1 and the phosphorylation level of Nrf2 15. Similarly, Li et al found that icariside II can improve oxidative stress in brain tissue of rats with CIR injury by activating Nrf2/HO-1 pathway 16.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2/HO-1 is an important antioxidant system. The Nrf2/HO-1 pathway has been reported to play an important role in I/R injury 15. Activation of the Nrf2/HO-1 pathway attenuates oxidative stress and inflammation caused by I/R injury, restores neurological deficits and reduces cerebral infarction volume 16.…”
Section: Introductionmentioning
confidence: 99%